How adaptive cruise control systems may increase congestion: Artikel - Rich, Jeppe; Sick Nielsen, Thomas (Proceedings from the Annual Transport Conference at Aalborg University, 2020)
It is appealing to believe that adaptive cruise control (ACC) systems, the forerunner of autonomous driving systems, will provide congestion relief by allowing for more efficient driving. In the paper, we investigate this hypothesis by comparing the time safety gap of ACC systems (across manufactures) with the observed revealed safety gap of human drivers. By clustering the safety gap within a network macroscopic fundamental diagram (MFD) of a large Danish motorway in the morning peak, it is concluded that; i) human drivers maintain a significantly lower safety gap when compared to the implied average safety gap of ACC enabled cars, and ii) the lower safety gap is efficient from an MFD perspective. Hence, with the ACC technology state of today and by applying standard settings, increased use of ACC is likely to contribute to more congestion.